2019
DOI: 10.1161/circulationaha.117.029015
|View full text |Cite|
|
Sign up to set email alerts
|

Hematopoietic Deficiency of the Long Noncoding RNA MALAT1 Promotes Atherosclerosis and Plaque Inflammation

Abstract: Background: The majority of the human genome comprises noncoding sequences, which are in part transcribed as long noncoding RNAs (lncRNAs). lncRNAs exhibit multiple functions, including the epigenetic control of gene expression. In this study, the effect of the lncRNA MALAT1 (metastasis-associated lung adenocarcinoma transcript 1) on atherosclerosis was examined. Methods: The effect of MALAT1 on atherosclerosis was determined in apolipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 40 publications
2
131
0
5
Order By: Relevance
“…In addition, MALAT1 was also up‐regulated in ox‐LDL treated macrophages, accompanied by increase of CD36 expression by recruiting β‐catenin to binding sites on the CD36 promoter . CD36 induced by MALAT1 could facilitate lipid uptake and promote subsequent atherosclerotic plaque formation …”
Section: Malat1 and Vascular Diseasesmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, MALAT1 was also up‐regulated in ox‐LDL treated macrophages, accompanied by increase of CD36 expression by recruiting β‐catenin to binding sites on the CD36 promoter . CD36 induced by MALAT1 could facilitate lipid uptake and promote subsequent atherosclerotic plaque formation …”
Section: Malat1 and Vascular Diseasesmentioning
confidence: 97%
“…Knockdown of MALAT1 caused increased plaque size and infiltration of inflammatory CD45 + cells partly via regulation of miR‐503 . Furthermore, MALAT1 were also involved in regulation of endothelial dysfunction, lipid accumulation and chronic inflammation, which contributed to development of atherosclerosis …”
Section: Malat1 and Vascular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has also been reported that lncRNAs involve in the pathogenesis of CVDs. For example, the lncRNA metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) was decreased in human plaques and down‐regulation of MALAT1 was correlated with poor prognosis of CVDs . LincRNA‐p21 was reported to regulate VSMC proliferation and atherosclerotic formation via the enhancement of p53 activity .…”
Section: Introductionmentioning
confidence: 99%